Effectiveness of adalimumab in treating patients with active psoriatic arthritis and predictors of good clinical responses for arthritis, skin and nail lesions. Issue 2 (7th October 2009) - Van den Bosch, F; Manger, B; Goupille, P; McHugh, N; Rødevand, E; Holck, P; van Vollenhoven, R F; Leirisalo-Repo, M; FitzGerald, O; Kron, M; Frank, M; Kary, S; et al.
Abstract : Objectives: To evaluate the effectiveness of adalimumab in patients with psoriatic arthritis (PsA) and identify predictors of good clinical response for joint and skin lesions. Methods: Patients received adalimumab 40 mg every other week in addition to standard therapy in this prospective, 12-week, open-label, uncontrolled study. Four definitions of good clinical response were used: ⩾50% improvement in American College of Rheumatology response criteria (ACR50), good response according to European League Against Rheumatism (EULAR) guidelines, a ⩾3-grade improvement in Physician Global Assessment of psoriasis (PGA) and a ⩾50% improvement in the Nail Psoriasis Severity Index (NAPSI). Response predictors were determined by logistic regression with backward elimination (selection level was 5%). Results: Of 442 patients, 94% completed 12 weeks of treatment. At week 12, 74%, 51% and 32% of the patients had achieved ACR20, 50 and 70, respectively; 87% and 61% experienced moderate and good responses according to EULAR criteria, respectively. The percentage of patients with PGA results of "clear/almost clear" increased from 34% (baseline) to 68%. The mean NAPSI score was reduced by 44%. No new safety signals were detected. A lower Health Assessment Questionnaire Disability Index (HAQ-DI) score, greater pain assessment, male sex and absence of systemic glucocorticoid therapy were strongly associated with achievement of ACR50 and good response according to EULAR criteria. In addition, greater C-reactive protein concentration and polyarthritis predicted ACR50, and non-involvement of large joints predicted a good response according to EULAR criteria. Conclusions: Adalimumab was effective in patients with PsA. Lower impairment of physical function, greater pain, male sex and no systemic treatment with glucocorticoids were factors that increased the chance of achieving a good clinical response.